2018
DOI: 10.1111/1755-6724.13545
|View full text |Cite
|
Sign up to set email alerts
|

Fenitized Wall Rock Geochemistry of the First Carbonatite Dyke at Bayan Obo, Inner Mongolia, China

Abstract: The first carbonatite dyke at Bayan Obo is well exposed on the surface for a length and width of approximately 60 m and 1.1–1.5 m, respectively. Along its strike, the fenitized H1 (Qs) and H2 (Cs) quartzite is replaced by Na‐amphiboles, aegirines, and alkali‐feldspars, intermittently stretching as far away as 800 m in length. Based on petrographical characteristics, the dyke's fenitized wall rocks are divisible into different zones: (1) outer, (2) middle, and (3) inner. The outer zone is 5–17 m from the NW mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The supra-subduction setting of the marble in a terrain intruded by alkaline rocks, and alteration of the marble to feldspar-rich rocks, suggests that the marble may be fenitized. Many examples of Nb mineralization, including mineralized limestones, are associated with fenitization (Elliott et al 2018), and fenitization is recorded at Bayan Obo (Wang et al 2018). Fenitization does occur in Northern Highlands of Scotland, cutting Moinian and Devonian rocks (Tanner and Tobisch 1972; Garson et al 1984) and attributed to latest Caledonian magmatism.…”
Section: Discussionmentioning
confidence: 99%
“…The supra-subduction setting of the marble in a terrain intruded by alkaline rocks, and alteration of the marble to feldspar-rich rocks, suggests that the marble may be fenitized. Many examples of Nb mineralization, including mineralized limestones, are associated with fenitization (Elliott et al 2018), and fenitization is recorded at Bayan Obo (Wang et al 2018). Fenitization does occur in Northern Highlands of Scotland, cutting Moinian and Devonian rocks (Tanner and Tobisch 1972; Garson et al 1984) and attributed to latest Caledonian magmatism.…”
Section: Discussionmentioning
confidence: 99%
“…The REE-bearing minerals are mainly hosted in the dolomitic rocks. The debate about whether the ore-hosting rock is sedimentary [1,[5][6][7][8][9][10][11][12] or igneous in origin [2][3][4][13][14][15][16][17][18][19][20][21][22][23][24][25] has lasted since the discovery of the deposit. Extensive application of advanced analytical techniques, such as in situ isotopic analysis, has demonstrated that the ore-hosting dolomitic rocks of the deposit are igneous in origin [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the main constituent mineral, dykes in the Bayan Obo ore district can be classified into calcitic, dolomitic, and calcite-dolomitic carbonatites [21,29,30]. Apart from some studies (e.g., [21]) reporting the bulk rock geochemical characteristics of some dolomite carbonatite dykes (Dol-dykes), most previous research has concentrated on a calcite carbonatite dyke (Cal-dyke) named the Wu dyke in the northeast of East Orebody [12,18,30,31], as this dyke contains extremely high REE contents up to 20 wt.% [31] and caused prominent fenitization of its country rocks. However, rocks from Cal-dykes cannot be related directly to the ore-hosting dolomites as they may be in different evolution stages of carbonatitic magmas [21,28,29].…”
Section: Introductionmentioning
confidence: 99%